ANALISIS PEMBENTUKAN KARAKTER SIKAP ILMIAH SISWA SEKOLAH DASAR MELALUI PENDEKATAN SAINTIFIK - Junnanto, Muhammad Wachid; Masithoh, Dewi (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2025)
The objective of this study was to examine the nature of scientific attitudes through the implementation of the scientific approach among fourth-grade students in elementary schools. This research is of the survey research variety. The research was conducted from January to September of 2023. The subjects of this study were fourth grade students in primary schools with a population of all students in SDIT Samawi Bantul. The research sample was obtained through the implementation of a simple random sampling technique, encompassing a total of 54 grade IV students, including 22 male students and 32 female students. The present study will utilize questionnaire guidelines to collect pertinent data. The research instrument employed was a closed-ended questionnaire. The study employed two distinct approaches to data analysis: descriptive statistics and inferential statistics. The analysis was conducted using SPSS 25. The findings of this study indicated that the character of scientific attitude can be cultivated in students enrolled in primary schools through the implementation of a scientific approach. The following characteristics are indicative of a scientific attitude: 1) environmental protection; 2) cooperation; 3) honesty; 4) curiosity; 5) creativity; and 6) critical thinking.